2000
DOI: 10.2337/diacare.23.11.1637
|View full text |Cite
|
Sign up to set email alerts
|

Linking pharmacy and laboratory data to assess the appropriateness of care in patients with diabetes.

Abstract: OBJECTIVE -To use pharmacy and laboratory data to assess diabetes care within a medical group and between medical groups and to determine dispensing patterns and the extent to which providers change therapy based on HbA 1c results.RESEARCH DESIGN AND METHODS -Participating groups submitted 1 year of data for continuously enrolled patients. Required data included date of birth, all diabetes-specific prescriptions (oral hypoglycemic agents and insulin), date of prescription, National Drug Code, all HbA 1c values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…This analysis was performed for selected agents. Secondary failure was defined as a patient adding one or more concomitant OHAs and/or switching from the initial OHA to a different agent (12,13). Finally, therapy change was defined as a combined utilization metric that included therapy augmentation, dosage adjustments (up or down), or switching to another OHA.…”
Section: Study Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis was performed for selected agents. Secondary failure was defined as a patient adding one or more concomitant OHAs and/or switching from the initial OHA to a different agent (12,13). Finally, therapy change was defined as a combined utilization metric that included therapy augmentation, dosage adjustments (up or down), or switching to another OHA.…”
Section: Study Definitionsmentioning
confidence: 99%
“…Another study by Wetzler and Snyder (13) described suboptimal control of type 2 diabetes with a monotherapeutic approach, showing that 27% of patients remained on the same monotherapy agent, even though they failed to achieve an HbA 1c level Ͻ8%. Another important aspect of this study was the evaluation of the mechanism and time to OHA therapy failure.…”
Section: Study Definitionsmentioning
confidence: 99%
“…Our study builds on the work of others (5,20) who have pointed to clinical inertia as a key barrier to effective diabetes management. Prior studies have identified several factors that are correlated with greater medication intensification, including absolute level of A1C (2,4) and systematic features of the clinical practice Our results must be interpreted in the context of the study design.…”
Section: Multivariate Modelsmentioning
confidence: 99%
“…The other selected indicators were sequential indicators that incorporate different levels of the longitudinal aspect of patient care, as identified in other studies looking at the evaluation of appropriate care. 14,15,21,26 Table 1 describes for each indicator the patients included in the numerator and denominator.…”
Section: Data Collection and Quality Indicatorsmentioning
confidence: 99%